2010
DOI: 10.1016/j.jacc.2010.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Risk Stratification, Discrimination, and Reclassification Improvement Based on Quantification of Subclinical Coronary Atherosclerosis

Abstract: CAC scoring results in a high reclassification rate in the intermediate-risk cohort, demonstrating the benefit of imaging of subclinical coronary atherosclerosis. Our study supports its application, especially in carefully selected individuals with intermediate risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
255
2
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 692 publications
(280 citation statements)
references
References 40 publications
11
255
2
12
Order By: Relevance
“…Furthermore, CAC scoring is associated to a very low effective radiation dose (~1.0 mSv) and it has been extensively validated as an independent predictor of major adverse cardiac events and total mortality in asymptomatic patients, providing a significant incremental value over traditional risk factors and functional studies (30)(31)(32)(33).…”
Section: Mini-reviewmentioning
confidence: 99%
“…Furthermore, CAC scoring is associated to a very low effective radiation dose (~1.0 mSv) and it has been extensively validated as an independent predictor of major adverse cardiac events and total mortality in asymptomatic patients, providing a significant incremental value over traditional risk factors and functional studies (30)(31)(32)(33).…”
Section: Mini-reviewmentioning
confidence: 99%
“…CAC scoring is a predictor of cardiovascular events and may add incremental prognostic value to conventional cardiovascular risk factors [33,34]. The relative risk of coronary events increased with increasing CAC burden, and clinically useful thresholds (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In the intermediate risk group (10e20% 10-year Framingham risk) from the HeinzeNixdorf Recall Study, CAC led to significant reclassification above traditional risk estimation [12]. Greenland et al also found the greatest utility of CAC in reclassifying the intermediate Framingham 10-year risk group [13].…”
Section: Cac and Cardiovascular Riskmentioning
confidence: 99%